Epidemiology of chronic kidney disease in Australian general practice: National Prescribing Service MedicineWise MedicineInsight dataset - Radford, Janette (Nephrology (Carlton), 2018)
AIM: To describe sociodemographic characteristics and comorbidities of a large cohort of Australian general practice‐based patients identified as having chronic kidney disease (CKD), using data from National Prescribing Service (NPS) MedicineWise's MedicineInsight dataset, and compare this dataset to the 2011–2012 Australian Health Survey's (AHS) CKD prevalence estimates. METHODS: This was a cohort study using deidentified, longitudinal, electronic health record data collected from 329 practices and 1 483 416 patients distributed across Australia, from 1 June 2013 until 1 June 2016. Two methods were used to calculate the CKD prevalence. One used the same method as used by the 2011–2012 AHS, based on one estimate of the estimated glomerular filtration rate (eGFR) or albumin/creatinine ratios (ACR). The other defined CKD more rigorously using eGFR or ACR results at least 90 days apart. RESULTS: In 2016, of 1 310 602 active patients, 710 674 (54.2%) did not have an eGFR or ACR test, while 524 961 (40.1%) had an eGFR or ACR test but did not meet AHS criteria for CKD. Age–sex adjusted rates of CKD (compared to AHS) were CKD 1–0.45% (3.9%), CKD 2–0.62% (2.5%), CKD 3a: 3.1% (2.7%), CKD 3b: 1.14% (0.6%), CKD 4–5: 0.41% (0.3%). The CKD cohort defined more rigorously using eGFR and ACR measures >90 days apart, had comorbidities of atrial fibrillation (30.5%), cardiovascular disease (25.0%), diabetes mellitus (17.1%) and hypertension (14.8%). CONCLUSION: The MedicineInsight dataset contains valuable and timely information about Australian patients with CKD, and provides prevalence estimates similar to those from AHS data.